Penentuan Kepadatan Tebar Lele yang Optimal Menggunakan Metode Integral Lipat Tiga - Alvi Sahrin Nasution; Bobby Putra Delon Togatorop; Kenjo Oktaviano Damanik; Lestari Novianti Sinurat; Monica Triyuni Sinaga; Widya Kartini Pangaribuan (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study aims to determine the ideal stocking density of catfish using the triple integral method. This mathematical method is applied to accurately calculate the volume of the cultivation pond and analyze the stocking amount and biomass projection at three different density levels, namely 50, 75, and 100 fish/m³. The calculation of the volume of the pond measuring 27 m x 11 m x 1.5 m produces a value of 445.5 m³. Based on the integral calculation, the optimal stocking amount is 22,275 fish, 33,413 fish, and 44,550 fish for each density, with the final biomass projection reaching 300.7 kg, 451.1 kg, and 600.4 kg, respectively. The analysis shows that the density of 100 fish/m³ produces the highest biomass, but its application must consider technical factors such as water quality, oxygen availability, and food competition. This method provides a solid and practical mathematical foundation for more efficient, scalable, and sustainable aquaculture planning.